Comparison of the outcomes of pull through suturing vs. tension band wiring fixation techniques in the management of patellar fractures - Kadam, Rahul; Pandey, Sachin; Challani, Abhay; Jain, Vicky; Shah, Akshay; Agarwal, Ankit (International Journal of Research in Orthopaedics, 2018)
Background: Operative fixation of displaced patella fractures has now become the standard of care. This study aims to asses functional outcomes, as well as identify complications in a patients treated with non-absorbable braided suture fixation for patellar fractures. These patients were then compared to a group of patients treated with K-wires with tension band wiring. Methods: This study was conducted on the patients admitted to orthopaedic ward at MGM medical college and hospital, Kamothe, Navi Mumbai. Total number of patients was taken for this study. Patients were followed up for a period of 6 weeks, 3 months, 6 months and at each visit. Patients were assessed by Lysholm knee score. Results: The mean age was 43.33 years for TB wiring group and 46.26 years for pull through suturing group. Out of 30, 15 were in TB wiring group in which 14 males and 1 female and, 15 in pull through suturing group 4 females and 11 males. The mean Lysholm knee score at 6 weeks for TB wiring group was 68.2 at 3 months was 81.4 at 6 months was 87. The mean Lysholm knee score for 6 weeks for pull through suturing was 69.2, at 3 months was 72.5 and at 6 months was 79.2. Conclusions: Patella fracture most common fractures, in this study we have discussed two modalities of treatment one is TB wiring and second is pull through suturing showing results that TB wiring have better results.